Models of good practice relevant to women & health : sexual and reproductive health and violence (Commonwealth Secretariat LondonGB, 2000)
Presents models collected from Commonwealth countries following the Commonwealth Health Ministers Meeting.
Keywords: REPRODUCTIVE HEALTH